2020
DOI: 10.1016/j.physd.2020.132444
|View full text |Cite
|
Sign up to set email alerts
|

Variable-density buoyancy-driven turbulence with asymmetric initial density distribution

Abstract: The effects of different initial density distributions on the evolution of buoyancy-driven homogeneous variable-density turbulence (HVDT) at low (0.05) and high (0.75) Atwood numbers are studied by using high-resolution direct numerical simulations. HVDT aims to mimic the acceleration-driven Rayleigh-Taylor and shock-driven Richtmyer-Meshkov instabilities and reveals new physics that arise from variable-density effects on the turbulent mixing. Here, the initial amounts of pure light and pure heavy flows are al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
4
14
0
Order By: Relevance
“…This led the authors to conclude that either a different scaling parameter might be required for higher-At experiments, or an asymptotic value of mass flux has not been reached. This indicates that different parameters may reach self-similarity at different Reynolds numbers; this has been further validated by recent computations of a triply periodic homogeneous variable-density mixing layer using direct numerical simulations [130][131][132]. Spectra of q 0 , v 0 and q 0 v 0 were measured using hot-wire anemometry, both q 0 and v 0 show approximately half to a decade of scales in the inertial range, the q 0 v 0 spectra did not show a clear indication of the-5/3 slope and were similar to the spectra at smaller Atwood numbers in GC1 [46].…”
Section: Measurements Of Velocity Density and Mass Fluxsupporting
confidence: 68%
“…This led the authors to conclude that either a different scaling parameter might be required for higher-At experiments, or an asymptotic value of mass flux has not been reached. This indicates that different parameters may reach self-similarity at different Reynolds numbers; this has been further validated by recent computations of a triply periodic homogeneous variable-density mixing layer using direct numerical simulations [130][131][132]. Spectra of q 0 , v 0 and q 0 v 0 were measured using hot-wire anemometry, both q 0 and v 0 show approximately half to a decade of scales in the inertial range, the q 0 v 0 spectra did not show a clear indication of the-5/3 slope and were similar to the spectra at smaller Atwood numbers in GC1 [46].…”
Section: Measurements Of Velocity Density and Mass Fluxsupporting
confidence: 68%
“…2 and 3 are the computational Reynolds number, Re 0 = ρ 0 L 0 U 0 /µ 0 , Schmidt number, Sc = µ 0 /ρ 0 D 0 , and Froude number, Fr 2 = U 2 0 /gL 0 ; where, µ 0 = µ * /rho * is the reference dynamic viscosity, ρ 0 is the reference density, and D 0 is the diffusion coefficient. In this study, we focus on the effects of acceleration reversal, so for all cases, both Sc and Fr numbers are equal to unity consistent with our previous studies on HVDT evolution under constant acceleration [4,5].…”
Section: Governing Equationssupporting
confidence: 62%
“…The initial conditions of the simulations are similar to our previous studies [3,4,5], where the initial density field has top- hat energy spectrum between wave-numbers 3 and 5 (see [5] for more details of the initialization). In addition, they all are initialized with a similar mixing state (θ 0 ≈ 0.07), where the non-dimensional mixing state measure (θ) is defined as…”
Section: Simulation Casesmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, recent work HVDT has been used to study structural changes to variable density turbulence when turbulent kinetic energy (KE) evolution is highly nonlinear. In HVDT under constant acceleration, a smooth transition from rapidly increasing to gradually decaying variable-density turbulence was observed that may be expected to persist in the more general case of RTI with constantand variable-acceleration profiles with smoother transitions and different variable-density flows such as Richtmyer-Meshkov instability (RMI), mixing layers, and jet flows [25][26][27].…”
Section: Introductionmentioning
confidence: 99%